Admission heart rate and in-hospital course of patients with Takotsubo syndrome. (15th December 2018) - Arcari, Luca; Limite, Luca Rosario; Cacciotti, Luca; Sclafani, Matteo; Russo, Domitilla; Passaseo, Ilaria; Marazzi, Giuseppe; Ansalone, Gerardo; Volpe, Massimo; Autore, Camillo; Musumeci, Maria Beatrice
Abstract: Background: In-hospital course of patients with Takotsubo syndrome (TS) is quite heterogeneous and life-threatening complications are not uncommon in the acute phase. The role of heart rate (HR) as a predictor of prognosis has not been sufficiently investigated in this setting. The study aims to assess the impact of HR at presentation on in-hospital course of patients with TS. Methods: The study population included 221 patients with TS enrolled in a multicentric registry. HR at admission was evaluated on the first electrocardiogram. According to tertile distribution of HR at presentation, 3 groups were identified: Group A (HR ≤ 76 beats per minute (bpm), n = 76), Group B (HR 77–95 bpm, n = 74) and Group C (HR > 95 bpm, n = 71). Acute in-hospital complications were defined as occurrence of severe pump failure and major arrhythmias. Results: 32 (14.4%) patients experienced complicated in-hospital course. HR on admission was significantly higher (108 bpm vs. 85 bpm; p < 0.001) and ejection fraction (EF) lower (35% vs. 40%; p = 0.009) in patients with complications than in those without. Patients in Group C experienced a 5-fold higher rate of complications compared to group A and B. After multivariate analysis, higher HR (odds ratio 1.34 per 10 bpm increase, 95% confidence interval (CI) 1.12–1.59; p = 0.001) and lower EF (odds ratio 1.24 per 5% decrease, 95% CI 1.01–1.54; p = 0.049) remained independently associated with a worse outcome. Conclusion: In a large population with TS, high HR on admission independently predicted complicated in-hospital course. Highlights: In-hospital course in Takotsubo syndrome is quite heterogeneous. Heart rate (HR) at admission independently predicts complications development. Complication rate is markedly increased in patients with HR >95 bpm. HR >95 bpm predicts complications development both in low- and high-risk patients.